Mangiferin Alleviates Mitochondrial ROS in Nucleus Pulposus Cells and Protects against Intervertebral Disc Degeneration via Suppression of NF-κB Signaling Pathway. (14th June 2021) - Yu, Haichao; Hou, Guowei; Cao, Jiankang; Yin, Yanyu; Zhao, Yunpeng; Cheng, Lei
Abstract : Intervertebral disc degeneration (IVDD), one of the most common clinical diseases worldwide, causes disc herniation and sciatica. Recent studies have identified the involvement of mitochondrial dysfunction, inflammatory responses, and extracellular matrix degradation in IVDD. Mangiferin is known to protect against various diseases by inhibiting oxidative stress, suppressing inflammation reaction, and relieving mitochondrial dysfunction. Whether mangiferin can alleviate IVDD remains to be elucidated. In the present study, human nucleus pulposus cells (HNPCs) and mouse intervertebral discs were cultured and stimulated with TNF- α, with or without treatment of mangiferin. Moreover, we established a rat needle puncture model and injected mangiferin into the intervertebral discs to verify its protective effect on IVDD. Furthermore, the activity of the NF- κ B signaling pathway was tested in vitro. Our results indicated that mangiferin alleviated the inflammatory response and reversed the loss of major intervertebral disc components. Besides, mangiferin reduced reactive oxygen species production, ameliorated mitochondrial damage, and decreased the expression of apoptosis-related parameters in stimulation of TNF- α . In addition, mangiferin antagonized the activation of the NF- κ B signaling pathway induced by TNF- α . Collectively, mangiferin antagonized mitochondrial ROS in NP cells and protected against IVDD by suppressing the activation of the NF- κ B signaling pathway, which might provide a potential therapeutic instrument for IVDD.